PENGARUH STRUKTUR KEPEMILIKAN, UKURAN PERUSAHAAN DAN KUALITAS AUDIT TERHADAP MANAJEMEN LABA - Fitria, Miftahul; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to test the influence of ownership structure, firm size, and audit quality to the earnings management. The result of this research shows that the variable which has significant influence to the earnings management is firm size. Firm size shows the positive result i.e. a large scale company has more complex operational activity compare to the small company; therefore it is more possible to do the practical of earnings management. Meanwhile, the variable of ownership structure and the audit quality do not have any significant influence to the earnings management.Keywords: Ownership Structure, Firm Size, Audit Quality, Earnings Management.